2012
DOI: 10.1002/etc.1884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triclosan on marine benthic and epibenthic organisms

Abstract: Triclosan is an antimicrobial compound that has been widely used in consumer products such as toothpaste, deodorant, and shampoo. Because of its widespread use, triclosan has been detected in various environmental media, including wastewater, sewage sludge, surface waters, and sediments. Triclosan is acutely toxic to numerous aquatic organisms, but very few studies have been performed on estuarine and marine benthic organisms. For whole sediment toxicity tests, the sediment-dwelling estuarine amphipod, Ampelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 58 publications
0
25
2
1
Order By: Relevance
“…These results were more sensitive than obtained from Perron et al (2012), which showed acute toxicity of TCS spiked sediments on estuarine amphipoda Ampelisca abdita and mysid Americamysis bahia. After 7-d exposure, the lethal concentration to amphipoda A. abdita and mysid A. bahia were 303 and 257 µg g -1 , respectively.…”
Section: Spiked-sediment Toxicity Assayscontrasting
confidence: 45%
See 1 more Smart Citation
“…These results were more sensitive than obtained from Perron et al (2012), which showed acute toxicity of TCS spiked sediments on estuarine amphipoda Ampelisca abdita and mysid Americamysis bahia. After 7-d exposure, the lethal concentration to amphipoda A. abdita and mysid A. bahia were 303 and 257 µg g -1 , respectively.…”
Section: Spiked-sediment Toxicity Assayscontrasting
confidence: 45%
“…Recent studies by Perron et al (2012) and Venkatesan et al (2012) with spiked sediments, estimated the pore water concentrations based on equilibrium partitioning to determine the effective concentrations in pore water (USEPA, 1993).…”
Section: Spiked-sediment Toxicity Assaysmentioning
confidence: 99%
“…We calculated concentrations of 137 and 10 mg/L triclosan in the interstitial water of the highand low-triclosan-treated mesocosms, respectively. Perron et al [9] reported a 96-h water-only LC50 for the amphipod A. abdita of 73 mg/L. The low-triclosan-treated mesocosms had predicted interstitial water concentrations below A. abdita's LC50, and no difference was noted for amphipods or the benthic community between the low-triclosan and the laboratory control mesocosms.…”
Section: Comparison With Aqueous Lc50smentioning
confidence: 99%
“…The 96-h aqueous median lethal concentration (LC50) for Americamysis bahia (mysid) and Ampelisca abdita (amphipod) is 74 and 73 mg/L, respectively [9]. For Palaemonetes pugio (grass shrimp), the acute aqueous LC50s were 305 mg/L for adult shrimp, 154 mg/L for larvae, and 651 mg/L for embryos [10].…”
Section: Introductionmentioning
confidence: 99%
“…Triclosan is a known water contaminant, and concerns persist about endocrine disruption in aquatic life, 167 which has led to inquiries about exposure levels and health effects in humans.…”
Section: Understanding the Incremental Clinical Benefit Of Tri-mentioning
confidence: 99%